Discriminating Green Beans of Puntang Arabica Coffees with 1H NMR Based-Metabolomics - Fahmi, Sofi Syamilatul; Happyana, Nizar (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
Puntang Arabica Coffee is one of the famous Indonesian coffees from West Java. This coffee is cultivated in the area of Mount Puntang, Bandung Regency. This study evaluated green beans of Puntang Arabica coffee obtained from different cultivating locations, including Cimulek, Cimenong, Ganda Paraja, and Nameur, with 1H NMR-based metabolomics. The green coffee bean samples were ground, extracted with D2O, and then measured with NMR spectroscopy. The obtained 1H NMR spectra were processed and evaluated by multivariate data analysis techniques using Orthogonal Partial Least Square Discriminant Analysis (OPLSDA) as the main model. In total, 20 metabolites were successfully identified in the 1H NMR spectra of Puntang coffees. Based on multivariate analysis, Cimulek and Cimenong coffee regions possessed similar metabolite profiles possibly due to being in proximity. Trigonelline, 5-chlorogenic acid, and citric acid were detected as the discriminant compounds for Cimulek and Cimenong coffees, whereas lactic acid, lipids, and stearic acid were associated with Ganda Paraja coffee. Meanwhile, GABA was detected constantly as the characteristic compound of Nameur coffee. This report revealed the metabolite profile of Puntang Arabica coffees for the first time and provided scientific information for the development of coffee plantations.